PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN JEMBATAN PERKEBUNAN DI DESA KANEYAN KECAMATAN TARERAN KABUPATEN MINAHASA SELATAN - Shania Fonika Intan Umboh; Elsje Pauline Manginsela; Vicky Richard Bernhard Moniaga (Sam Ratulangi University, 2020)
This study aims to describe how the level and form of community participation in the construction of plantation bridges in Kaneyan Village, Tareran District, South Minahasa Regency. The study was conducted in November 2019 until April 2020. The data used in this study are primary and secondary data. Primary data were obtained through direct interviews with 30 respondents using a questionnaire and secondary data obtained from the Kaneyan village government office. The sampling technique was done intentionally (purposive sampling). Analysis of the data used in the research is a descriptive analysis method by making tables and percentages to explain the level and form of community participation in the construction of plantation bridges. Measurement of the level of participation using a Likert Scale. The results showed that the level of participation of the Kaneyan Village community in the plantation bridge construction program at the planning, implementation and maintenance stages and in the form of mind, energy, skills and goods participation was at a percentage of 57.51% included in the Participating category.*eprm*